MENGGAGAS KODE ETIK AKUNTAN PUBLIK DALAM BINGKAI NILAI KEARIFAN LOKAL BUDAYA BUGIS - Romy Nugraha Js; Syamsu Alam; Asriani Junaid (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
With knowledge, understanding, a better willingness to apply moral and ethical values adequately to reduce various ethical violations, it is necessary to have an in-depth study from various perspectives on the ineffectiveness of the application of accounting professional ethics in Indonesia. This study wants to provide a new perspective to initiate a code of ethics for public accountants with the perspective of local wisdom values for Bugis culture. This type of research is classified as a qualitative descriptive study using a Postmodern Ethnographic approach. This research data collection method from the results of interviews with informants using Spradley's ethnographic method. The results of this study indicate that the combination of the values of the life of lempu, getteng, warani and acca can strengthen auditors in holding tight to the principles of integrity, objectivity, competence and confidentiality in the code of ethics, which are wrapped in the values of siri 'life that make public accountants professional in carrying out their work and added work motivation with reso life values, all the values of life will be integrated into the soul in a public accountant. Keywords: Ethics; Code of Ethics; Bugis Cultural Local Wisdom Values.